Assessing Information System Performance in Banks Based on Multi-Criteria Decision Making Techniques - Daghouri, Ansar; Mansouri, Khalifa; Qbadou, Mohammed (International Journal of Engineering and Technology, 2018)
The objective of this paper is to introduce a new technique to evaluate and analyze the performance of information system based on the DeLone and McLean information systems success model. The technique presented is derived from the research done on measuring information system success and multi criteria decision making techniques. In this work, a framework has been developed to select the most performing information system via a combined approach of two most popular methods: AHP and TOPSIS. The work methodology consists of three main steps. In first step, the main criteria are chosen from the Delone and McLean model (2003). In the second step, the weights of the main criteria and sub-criteria are calculated using the AHP method. In the final step, alternatives are ranked by using TOPSIS. A demonstration of this methodology on five Moroccan banks is presented.Â Â